2002
DOI: 10.1023/a:1019814713428
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Asp and Asn residues, located in a loop structure of rhIL-11, undergo isoAsp formation under stressed conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…It has been reported that isomerization and deamidation reactions occur during the isolation, purification, and storage of proteins such as recombinant calmodulin, 9) recombinant human growth hormone, 10) tissue plasminogen activator, 11) synapsin I, 12) tubulin, 13) recombinant interleukin-11, 14) and recombinant monoclonal antibody. 15) Isoaspartate has also been identified in a variety of cellular proteins, including erythrocyte membrane protein 4.1, 16) phosphacan, 17) ribosomal protein S11, 18) histone H10, 19) histone H2B, 20) Bcl-x L , 21,22) cAMP-dependent protein kinase (PKA), 23) and collagen type I 24) in vivo.…”
Section: Isoaspartates In Damaged and Aged Pro-teinsmentioning
confidence: 99%
“…It has been reported that isomerization and deamidation reactions occur during the isolation, purification, and storage of proteins such as recombinant calmodulin, 9) recombinant human growth hormone, 10) tissue plasminogen activator, 11) synapsin I, 12) tubulin, 13) recombinant interleukin-11, 14) and recombinant monoclonal antibody. 15) Isoaspartate has also been identified in a variety of cellular proteins, including erythrocyte membrane protein 4.1, 16) phosphacan, 17) ribosomal protein S11, 18) histone H10, 19) histone H2B, 20) Bcl-x L , 21,22) cAMP-dependent protein kinase (PKA), 23) and collagen type I 24) in vivo.…”
Section: Isoaspartates In Damaged and Aged Pro-teinsmentioning
confidence: 99%
“…If the enzyme is not able to reach the isoaspartic acid it cannot convert it and therefore the number would be low. This would suggest that previous work with this enzyme may be underestimating the amount of isoaspartic acid [22,24].…”
Section: Development Of Pimt Methodsmentioning
confidence: 97%
“…8 using an optimized VHPLC method. The LC method was significantly improved over previously utilized methods [22,24] based on time and limit of detection using a small particle size column. The entire LC method including cleaning was reduced to 4.5 min as compared to a suggested method of 13 min.…”
Section: Development Of Pimt Methodsmentioning
confidence: 99%
“…To confirm the identity of LCC1 and LCC2, we utilized an additional endoprotease, Asp-N. It is known that Asp-N cannot cleave peptide bonds N-terminal to isoAsp [35]. Therefore, it was hypothesized that LCC1 and LCC2 should generate different fragments by Asp-N, if they contain isoAsp and Asp, where the native peptide contains Asn in the same position.…”
Section: Selective Digestion By Asp-nmentioning
confidence: 99%